СРК сочетающаяся с нейроциркуляторной дистонией: воспаление, клиническое течение, эффективность лечения - Прилуцкая, О.А.; Лесниченко, Д.А. (Таврический медико-биологический вестник, 2009)
Проведено дослідження показників у хворих на СРК, що характеризують

запалення й зв’язки їх з наявністю нейроциркуляторної дистонії. У хворих на СРК із

наявністю супутньої НЦД має місце достовірне підвищення інтенсивності

запалення, про що свідчать підвищені середні рівні СРБ та інтерлейкіну-8, а також

питома вага осіб з більш високими їхніми концентраціями. Установлено

достовірний взаємозв’язок величини індексу Кердо зі ступенем важкості СРК,

інтенсивністю ряду клінічних і психологічних показників, а також рівнем СРБ,

інтерлейкіну-8. Установлено достовірну кореляцію наявності НЦД із концентрацією

С-реактивного білка, IL-8. The article represents a study of indicators of inflammation and their relation to the

presence of neurocirculatory dystonia in patients with IBS. Patients with IBS and

associated NCD have a definite increase of inflammation intensity, this is indicated by

higher average levels of CRP and interleukin-8, as well as the proportion of persons

with higher concentrations. A reliable value of the Kerdo index relationship with the

gravity of the IBS, intensity of a number of clinical and psychological indicators, as well

as the level of CRP, interleukin-8 has been found. Also, a definite correlation with the

presence of NCD with concentration of Creactive protein, IL-8 has been established.